Mechanisms and challenges of renewable energy cooperation in Northeast Asia - Huaicun, Zhang; Yuna, Kim; Kada, Yukiko (Pt. Riset Press International, 2023)
In recent decades, sustainable economic growth has caused an increase in energy consumption in North Asia, especially in China, Japan and South Korea. However, internal supply cannot meet energy demand, bringing two related consequences: First, the enlargement of the gap between production and consumption leads to dependence on external energy sources. Second, forcing the government to map its energy policy. However, unlike other regions such as the European Union and the Association of Southeast Asian nations, the dependence of the Energy of Northeast Asia has not caused the closest intra-regional cooperation. Conversely, in some cases, it damages cooperation and worsens non -constructive competition. Therefore, in this study, we aim to highlight the problematic relationship between energy securitization and regional energy cooperation in Northeast Asia and provide an analysis of the reasons, mechanisms and challenges for regional cooperation led by energy. In this case, we think that, by exploiting regional compatibility in the generation of renewable energy and in the consumer model, building a mechanism of integration and multimodal communication will promote greater integration and contribute to filling the gap between securitization and energy cooperation in the east and work the same in the east and working with Asia.